Characterization and identification of newly isolated Acinetobacter baumannii strain Serdang 1 for phenol removal - Mohamad Yadzir, Zailatul Hani; Abd. Shukor, Mohd. Yunus; Nazir, Muhammad Shahid; Abdullah, Mohd Azmuddin (American Institute of Physics, 2012)
A new indigenous bacterial strain from Malaysian soil contaminated with petroleum waste had been successfully isolated, characterized and identified for phenol removal. The gram negative bacteria showed 98% identity with Acinetobacter baumannii based on Biolog™ Identification System and the determination of a partial 16S ribosomal RNA (rRNA) sequence. The isolate clustered with species belonging to Acinetobacter clade in a 16S rDNA-based neighbour-joining phylogenetic tree.